Stars & planets - Goldsmith, Mike, 1962- (New York ; London : Kingfisher, 2008)
A visual guide to the universe, galaxies, and solar systems.
Stars -- The universe -- Galaxies -- Solar system -- The sun -- Mercury and Venus -- Earth -- Mars -- Jupiter and Saturn -- Uranus and Neptune -- Space rubble -- Space clouds -- Strange stars -- Star death -- Space warps -- Space pioneers -- Beyond the sky -- Cities in the sky -- Starships -- Life beyond.
Includes bibliographical references (p. 48) and index.
Keywords: Stars -- Juvenile literature; Planets -- Juvenile literature; Astronomy -- Juvenile literature; Stars; Planets; Astronomy